Downscaling albedo from moderate-resolution imaging spectroradiometer (MODIS) to advanced space-borne thermal emission and reflection radiometer (ASTER) over an agricultural area utilizing aster visible-near infrared spectral bands - Mokhtari, Mohammad H. (Academic Journals, 2011)
Due to the limitation in spatial and spectral resolution, a few numbers of satellite data are applicable in field scale surface Albedo modeling. ASTER was an alternative for surface energy balance modeling, but since April 2008, shortwave detector has stopped recording due to the high-abnormal-temperature problem. Beside, temporal resolution of ASTER is insufficient for field-scale monitoring of surface parameters. Thus, this study was aimed first; to examine the capability of ASTER VNIR bands in estimation of surface Albedo and second, to downscale Albedo from MODIS to ASTER using Albedo resulted from ASTER VNIR bands. Combination of these two stages is expected to be a solution for field scale monitoring of surface Albedo from MODIS and ASTER data acquired after April 2008. Results confirmed that bands 1 and 3 which is available after April 2008 on ASTER data can be modeled for estimation of surface Albedo with less than 0.024% loss of information where land cover consist of soil and vegetation. From four downscaling methods, namely FSIM, PBIM, wavelet transfer and high pass filter (HPF) examined in this study, we also found that the most precise subpixel estimate were obtained by FSIM downscaling method (R2 = 0.96, RMSE = 0.01); although, the outputs of three other methods were significant.